SYMBOLIC INTERACTION OF BAMBANGAN CAKIL DANCERS AT WEDDINGS IN REMBANG REGENCY - Anom Sutejo; Pebrianti, Sestri Indah (Acintya, 2024)
Bambangan Cakil dance performance at a wedding event in Rembang Regency has its own characteristics. In every performance there is interaction between the dancers and the audience. This article aims to describe and explain the performance form of Bambangan Cakil Dance at weddings in Rembang Regency as well as understand and analyse the process of symbolic interaction in the performance. The research method used is qualitative and uses an etic and emic approach, so that researchers can see the differences between the views of researchers and the views of people who see the same performance. The results showed that the form of Bambangan Cakil dance performance has a structure consisting of the beginning, core, and end of the performance. Bambangan Cakil dance performances also contain elements including themes, storylines, dancers, expressions, movements, music, makeup, clothing, props, and stages. The symbolic interaction of Bambangan Cakil dancers is divided into three parts, namely before the performance there are interactions: 1) dancers with dancers, 2) dancers with guests, and 3) dancers with sound system operators. During the performance there are interactions: 1) dancers with dancers, 2) dancers with bridal couples, and 3) dancers with guests. At the end of the performance there are interactions: 1) dancers with dancers, 2) dancers with bridal couples, 3) dancers with guests, and 4) dancers with sound system operators.